ANALISIS RASIO KEUANGAN TERHADAP PEMBAGIAN SISA HASIL USAHA PADA KOPERASI KREDIT ANUGERAH BANDARJAYA LAMPUNG TENGAH - Agnes Susana Merry Purwati (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2019)
Financial ratio is to be an analytical tool that have an important influence the progress andsuccess of a company in managing its finances. For the case of the research, the Anugerah CreditUnion Bandarjaya is the object to be researched by the author. In this research, the authors tooks theresearch variable such us Liquidity, Solvability, and Rentability Ratio based on variable Remaining ofBusiness Results (SHU).The purpose of the research is to find out the influence of Liquidity Ratio, Solvability Ratio, andRentability Ratio to the result of Remaining of Business Results (SHU). The author hopes that in thenext period the Anugerah Credit Union Bandarjaya can improve its efficiency and effectiveness infinancial performance. This is based on the year of the research period, there is a decrease in theRemaining of Business Results (SHU).The results of the research shows that the Liquidity Ratio (Current Ratio) has influencedpositively and significantly on the Remaining of Business Results (SHU), the Solvability Ratio (Debt toEquity Ratio) has influenced positively and significantly on the Remaining of Business Results (SHU),the Rentability Ratio (Return On Equity) has influenced positively and significantly on the Remaining ofBusiness Results (SHU). Simultaneously (together), Current Ratio (CR), Debt to Equity Ratio (DER),and Return On Equity (ROE) has influenced positively and significantly on the Remaining of BusinessResults (SHU) in Anugerah Credit Union Bandarjaya.